2007
DOI: 10.5144/0256-4947.2007.1
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus-16/18 cervical infection among women attending a family medical clinic in Riyadh

Abstract: BACKGROUNDPrevalence information is lacking on human papillomavirus types 16 and 18 (HPV-16/18) infection in cervical tissues of women residing in Riyadh, Saudi Arabia. In addition, there are no observations on progression to cervical intraepithelial neoplasia (CIN).SUBJECTS AND METHODSPap smear and HPV-16/18 DNA detection by PCR followed by Southern blotting was performed on 120 subjects (Saudi and other Arab nationals) during routine gynecological examination. Some HPV-positive subjects were followed for 4 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
(23 reference statements)
2
18
1
Order By: Relevance
“…This rate was considered relatively high given the fact that in Saudi Arabia extramarital sex and multiple sexual partnerships are strictly prohibited. [17] Other studies in Middle Eastern countries reported much lower prevalence rates like 4.9% in Lebanon [24] and 2.7% in Kuwait. [25] While in South American countries, which have the highest incidence rate of cervical cancer, the prevalence reached 20.4%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This rate was considered relatively high given the fact that in Saudi Arabia extramarital sex and multiple sexual partnerships are strictly prohibited. [17] Other studies in Middle Eastern countries reported much lower prevalence rates like 4.9% in Lebanon [24] and 2.7% in Kuwait. [25] While in South American countries, which have the highest incidence rate of cervical cancer, the prevalence reached 20.4%.…”
Section: Discussionmentioning
confidence: 94%
“…[16] While no data is available about the prevalence of HPV among women in UAE. [2] Some studies in Riyadh (KSA) and Qatar have showed a prevalence of 31.8 [17] and 64% in these two countries, respectively. [18] Early detection of cervical cancer, which can be achieved by regular screening, offers the chance to a more effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HPV-16 alone was 13.3% and HPV-16 as a mixed infection with HPV-18 was 15%, totaling 28.3% for all HPV-16 infections. The prevalence of HPV-18 alone was 3.3%, hence 18.3% for all HPV-18 infections [32]. A study from the western region of Saudi Arabia examined 40 cervical specimens using PCR and BioFilmChip microarray hybridization and reported positive HPV infections in the cervical specimens of 43% of the women, indicating an alarming rate of HPV infection in Saudi Arabia [33].…”
Section: Hpv Prevalence In the General Population In Saudi Arabiamentioning
confidence: 99%
“…Another study described a relatively high prevalence of HPV-16 or HPV-18 cervical infections among women attending a family medicine clinic in Riyadh (capital city of Saudi Arabia) [32]. The HPV-16/18 DNA detection with PCR followed by Southern blotting was performed on 120 women in Riyadh [29] (Saudi and other Arab nationals) during their routine gynecological examinations.…”
Section: Hpv Prevalence In the General Population In Saudi Arabiamentioning
confidence: 99%
“…One study investigated HPV 16/18 DNA prevalence among women attending a family medicine clinic for routine gynecological examinations in Riyadh, the capital of Saudi Arabia. In total, 120 cervical swab specimens were collected and analyzed using PCR followed by Southern blotting [20]. The overall prevalence of HPV 16/18 was 31.6%.…”
Section: Hpv and Cervical Cancer In Arabian Peninsula Countriesmentioning
confidence: 99%